Effect of Adding Different Levels of Powdered Leaves of the Moringa Tree on Reproductive Performance and Egg Traits of Female Japanese Quails - Noaman, H. A. (American Journal of Botany and Bioengineering, 2026)
In the current experiment, we investigated the impact of dietary supplementation of Moringa oleifera leaf powder (MOLP) on the egg production rate and quality traits of Japanese quails ( Coturnix japonica) reared. The experiment was carried out between the 27 October 2023 and 26 November 2023 at the Poultry Farm in the Department of animal production, Kirkuk University College of Agriculture. A completely randomized study was used to randomly distribute 57 healthy female quails to four dietary treatments: T1 (control 0% MOLP), T2 (5%), T3 (7.5%), and T4 (10%), which were further subdivided into 6 replications each. Birds were kept in normal conditions of management and fed and watered at will during the course of the experiment. The external egg traits (egg length, egg breadth, index of shape, egg volume, surface area, and shell thickness), internal weight traits (egg weight, yolk weight, albumen weight, shell weight, yolk index, albumen index, and shell index) and dimensional traits (albumen height and diameter, yolk height and diameter) as well as percentage based indices (yolk, albumen, shell percentages, yolk index, albumen index, and shell index) were measured on a daily basis. The results showed that the MOLP supplement made a significant impact on all the parameters of egg length, breadth, volume, and surface area (p ≤ 0.001), but the egg shape index was not affected. Higher levels of inclusion (T3 and T4), eggshell thickness and indices of shell improved significantly, with T4 recording the highest improvement (p ≤ 0.01). Internal features (egg, yolk, albumen) weightings reduced significantly in the supplemented groups relative to the control ones (p 0.001) but indices of yolk and albumen were not significantly altered. It did not show any age difference between treatments at first oviposition. Overall, the MOLP supplementation had a balanced effect, whereby the greater the inclusion level, the more adverse effects came with respect to the egg size and internal quality parameters, but the greater the effect the supplement had in enhancing the shell thickness, weight and structural indices. Supplementation (5-7.5% is adequate) could enhance the quality of the shells, without decreasing egg mass, even at high supplementation levels, which would have implications on quail egg production.